Overview of Maternal Near Miss in a Teaching Hospital in Eastern Nepal - Chaudhary, Amar Nath; Baral, Gehanath; Subedi, Shanti; Kaphle, Pratibha; Shah, Rajan Kumar (Journal of Nobel Medical College, 2024)
Background: A maternal near-miss case study measures life-threatening pregnancy complications and allows the assessment of the quality of obstetric care. Materials and Methods: A Cross-Sectional study was carried out for a year in the maternity ward of a teaching hospital and a descriptive analysis was performed. Results: There were 162 maternal near-miss cases, 9 maternal deaths, and 6779 live births witha maternal near-miss ratio of 23 per 1000 live births. The mean age of the near-miss women was 26.4±6.3 years. Haemorrhage, hypertensive disease in pregnancy, ruptured uterus, and ICU admissions are the commonest complications arising in such cases. Conclusion: Maternal near-miss incidence is similar to global data but the mortality indexappears slightly